Two new combinations in the genus Chionanthus L. (Oleaceae) (Bangladesh Journal of Plant Taxonomy, 2014)
Not available.DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21361Bangladesh J. Plant Taxon, 21(2): 197-198, 2014 (December)